2012
DOI: 10.3892/or.2012.2024
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine inhibits growth of human cervical cancer cells through the induction of apoptosis

Abstract: Sanguinarine, a natural benzophenanthridine alkaloid, has been shown to possess anticancer activity in vitro and in vivo. In the present study, we demonstrated that sanguinarine caused a dose-dependent inhibition of growth in HeLa and SiHa human cervical cancer cells, i.e., 2.43 µmol/l (IC50) in HeLa cells and 3.07 µmol/l in SiHa cells. Cell cycle analysis revealed that sanguinarine significantly increased the sub-G1 population, from 1.7 to 59.7% in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Earlier studies have documented that A. mexicana is likely to contain benzylisoquinoline alkaloids such as benzophenanthridines, sanguarine, rotoberberines and protopines, protomexicine, mexitin dehydrocorydalmine, jatrorrhizine, columbamine, dl-tetrahydrocoptisine and dihydrocoptisine [21,22,23,24,25,26]. In an independent study on rodents [22], A. mexicana extracts were found to be effective in curing ulcers induced with cystamine.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have documented that A. mexicana is likely to contain benzylisoquinoline alkaloids such as benzophenanthridines, sanguarine, rotoberberines and protopines, protomexicine, mexitin dehydrocorydalmine, jatrorrhizine, columbamine, dl-tetrahydrocoptisine and dihydrocoptisine [21,22,23,24,25,26]. In an independent study on rodents [22], A. mexicana extracts were found to be effective in curing ulcers induced with cystamine.…”
Section: Discussionmentioning
confidence: 99%
“…A down-regulation of pro-caspase 3, Bcl-2, clAP2, XIAP, and c-FLIPs [20,52] has been also observed in basal cell-like MDA-MB-231 human breast carcinoma cells treated with sanguinarine. The effect of sanguinarine treatment has been evaluated also on the expression levels of Bax and Bcl-2 proteins in immortalized human keratinocytes (HaCaT) [24,25] , human leukaemia JM1 and K562 cells [35] and in Hela and SiHa human cervical tumor cells [53] . These findings indicate that sanguinarine, depending on the dose employed, down-regulates the expression levels of Bcl-2 protein while increasing those of Bax protein, which is a key regulator of mitochondrial damage.…”
Section: Sanguinarine Induces Apoptosis In Tumor Cellsmentioning
confidence: 99%
“…In fact, sanguinarine induces apoptosis in a variety of cancer cells after cell cycle arrest (Adhami et al, 2004), caspase activation (Kim et al, 2008), depletion of cellular GSH (Debiton et al, 2003), modulation of Bcl-2 family members (Ahsan et al, 2007;Lee et al, 2012;Xu, et al, 2012), and upregulation of death receptor 5 [DR5; tumor necrosis factor-related apoptosis-inducing ligand R2 (TRAIL-R2)] (Hussain et al, 2007). Of note, it has been observed that sanguinarine sensitizes human gastric adenocarcinoma cells to TRAIL-mediated apoptosis (Choi et al, 2009) and that it induces apoptosis of human osteosarcoma cells through the extrinsic pathway (Park et al, 2010).…”
Section: Introductionmentioning
confidence: 99%